The Optimization of Photovoltaic Systems Design Using Mathematical Modeling and QFD-DSM Methods - Marziyeh Kashani; Atefeh Amindoust; Mahdi Karbasian; Abbas Sheikh Aboumasoudi (Majlesi Journal of Electrical Engineering)
In today's industrialized world, to survive in competitive markets, businesses are required to identify the expectations of their customers, whether explicitly or implicitly, and focus on these needs from the planning to the operational level.  To produce customer-oriented products, it is important to extract design requirements that meet the identified needs. The purpose of the present study, which has been done on Photovoltaic systems (PV), is to develop a model for the selection of the optimal components required to design a new product. In this regard, Customer Needs (CNs) which have been extracted from the first stage of the systems engineering process have been interpreted to Functional Requirements (FRs) using the first matrix of QFD. They have examined and prioritized by use of Analytical Network Process (ANP). Then FRs have entered the second matrix of QFD and examined along with leveled components based on the alternatives available for each component. Also, the Design Structure Matrix (DSM) has been used to evaluate the effect of elements upon each other in each phase. Finally, the optimal components are selected by the presented multi-objective mathematical model. Accurate assessment of customer needs using a systems engineering framework in addition to extracting important functional requirements to meet the needs as well as selecting the optimal components for new product design, by integrating the three methods QFD, ANP and DSM, using multi-objective mathematical modeling has not been done by other researchers so far.